Respon Pertumbuhan Udang Vaname (Litopenaeus vannamei) terhadap Pakan Ekstrak Daun Jarak Pagar (Jatropha curcas) dengan Dosis Berbeda - Ansani Takwin, Bagus; Hari Aditia Pratama, Muhammad (Journal of Microbiology, Biotechnology and Conservation, 2025)
Pacific white shrimp (Litopenaeus vannamei) is a leading aquaculture commodity in Indonesia, valued for its high nutritional content, rapid growth, and disease resistance. However, pathogenic infections such as Vibrio spp. can cause mortality rates of up to 100% within a day, necessitating strategies to enhance immune function. This study aimed to evaluate the effect of incorporating Jatropha curcas leaf extract into feed on the growth performance and survival of L. vannamei. The experiment was conducted for 60 days using a Completely Randomized Design with four treatments: control (no extract), 1%, 2%, and 3% J. curcas leaf extract, each with three replicates. Parameters measured included absolute weight gain, absolute length gain, specific growth rate (SGR), feed conversion ratio (FCR), and survival rate (SR). Results showed that the 3% treatment (JC3) achieved the highest absolute weight gain (6.37 g), significantly higher (p<0.05) than the control and JC1, but not significantly different from JC2. The highest SGR was also recorded in JC3, while the lowest FCR (1.2) was observed in JC3, which was not significantly different from the control. The improved growth performance with J. curcas supplementation is likely attributed to its bioactive compounds, such as tannins and flavonoids, which possess antibacterial and immunostimulant properties, thereby enhancing shrimp health and feed utilization efficiency. This study recommends a 3% inclusion level of J. curcas leaf extract in feed as an optimal dose to support the growth of L. vannamei.